High-resolution dielectronic recombination experiments at the upcoming CRYRING@ESR facility. (July 2015) - Brandau, C; Lestinsky, M; Kozhuharov, C; Müller, A; Schippers, S; Stöhlker, Th
Synopsis: The heavy ion storage ring CRYRING formerly located at the Manne-Siegbahn-Laboratory (MSL) in Stockholm, Sweden was dismantled and transferred to the GSI-Helmholtzzentrum für Schwerionenphysik (GSI) in Darmstadt, Germany and is presently being rebuilt. At its new location at GSI's storage ring ESR, the ultracold electron beam of the CRYRING electron cooler will allow for a new generation of high-resolution dielectronic recombination experiments with highly charged heavy ions and radioisotopes.